2013
DOI: 10.1007/s11046-013-9642-3
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Sertaconazole Cream (2 %) in Diaper Dermatitis Candidiasis

Abstract: AimDiaper dermatitis (DD) is an inflammatory irritating condition that is common in infants. Most cases are associated with the yeast colonization of Candida or diaper dermatitis candidiasis (DDC), and therefore, the signs and symptoms improve with antimycotic treatment. Sertaconazole is a broad-spectrum third-generation imidazole derivative that is effective and safe for the treatment for superficial mycoses, such as tineas, candidiasis, and pityriasis versicolor. Our goal was to assess the efficacy and safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
(38 reference statements)
0
14
0
5
Order By: Relevance
“…This upward trend is concerning considering the limited number of antifungal drugs available. 5 Therefore, there is an urgent need for the development of new antifungal agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This upward trend is concerning considering the limited number of antifungal drugs available. 5 Therefore, there is an urgent need for the development of new antifungal agents.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ADRs, such as kidney damage, hypokalemia, and even thrombophlebitis, are also common and may be occasionally serious. 5 The lipid formulations of AMB may alleviate the toxicity and increase the bioavailability of AMB. 5,6 Nevertheless, the high cost of these formulations puts them beyond the reach of most of patients with fungal infection.…”
mentioning
confidence: 99%
“…In multiple clinical studies, mycosis has been isolated in up to 80% [6] of children with DD which can be present for even three or more days [7]. Once the stratum corneum has been damaged the skin is more vulnerable to secondary infections by bacteria and fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Once the stratum corneum has been damaged the skin is more vulnerable to secondary infections by bacteria and fungi. Ferrazzini [7] found that colonization with Candida albicans was significantly increased in children with symptomatic diaper rash. A wide variety of other infections has been reported but it appears that Candida is the most common opportunistic invader in diaper areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation